Penyelenggaraan Pelayanan Go Digital pada Identitas Kependudukan Digital (IKD) dalam Perspektif Dynamic Governance di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Tangerang - Vivi Charunia Wati; Trisya Walza Rizkita; Bagus Sajiwa; Rifdah Silawarti; Eko Prasetyo (Public Service and Governance Journal, 2024)
Dynamic governance refers to government activities continuing in the process of public policy governance that can reach long-term interests. This research uses a qualitative approach with a descriptive method and the key informant is the Population and Civil Registration Office of Tangerang Regency. Data collection techniques were conducted through interviews, field observations, and documentation. The purpose of this research is to find out the implementation of Digital Population Identity through the perspective of Dynamic Governance at the Population and Civil Registration Office of Tangerang Regency. The results showed that dynamic capabilities in the implementation of Digital Population Identity services are able to produce various changes that have an impact on improving the quality of public services, but there are still obstacles such as low public understanding of using Digital Population Identity (IKD) and not all government agencies can accept the process of verifying population data with Digital Population Identity (IKD). Therefore, the dynamic capability process in the Digital Population Identity (IKD) service is influenced by three indicators, namely thinking ahead, thinking again, and thinking across as well as two driving factors, namely able people and agile process.